Hybrid mini-thoracotomy for Brugada syndrome: epicardial substrate characterization and ablation—results from UNCOVER(BrS) study - Iacopino, Saverio; Sorrenti, Paolo Francesco; Petretta, Andrea; Colella, Jacopo; Di Vilio, Alessandro; Statuto, Giovanni; Fabiano, Gennaro; Campagna, Giuseppe; Peluso, Gianluca; Fabiano, Emmanuel; Indellicati, Giuseppe; Brogneri, Simona; et al. (Frontiers in Cardiovascular Medicine, 2025)
BackgroundData on the safety and efficacy of thoracotomy epicardial ablation for Brugada syndrome (BrS) are limited. The ongoing UNCOVER(BrS) trial aims to evaluate epicardial substrate homogenization in patients with symptomatic BrS.ObjectiveTo report the study design and preliminary outcomes of a novel hybrid mini-thoracotomy approach for Brugada substrate mapping and ablation in an initial cohort of patients with BrS.MethodsThis independent, prospective pilot study was conducted at a single center. Patients with BrS who had an implantable cardioverter-defibrillator (ICD) and a history of symptomatic events (syncope and/or documented ventricular arrhythmia) were selected for epicardial ablation. Following surgical access via mini-thoracotomy, substrate mapping was performed using the Advisor™ HD Grid catheter to identify the pathological substrate after an ajmaline infusion. Point-by-point ablation with a contact force catheter was performed to achieve substrate homogenization.ResultsBetween January 2022 and July 2024, six patients were enrolled. No major acute peri-, or post-procedural complications were observed. The procedure acutely eliminated all pathological substrates, with complete suppression of the Brugada ECG pattern. Procedural efficiency improved over time, with a progressive reduction in procedural duration. At the 12-month follow-up, none of the patients had any symptomatic arrhythmic events. Omnipolar mapping demonstrated superior delineation of the arrhythmic substrate compared to bipolar mapping.ConclusionEpicardial substrate ablation via a hybrid mini-thoracotomy approach was found to be technically feasible and preliminarily safe in this initial assessment. No acute or long-term major adverse events were observed. By the 12-month follow-up, no symptomatic arrhythmic episodes had occurred. Larger studies with extended follow-up durations are needed to validate these initial findings.Trial registrationClinicalTrials.gov identifier: NCT05643209. Funded by Abbott Medical.